Pharmaceutical care in digital revolution : blending digital with human innovation. - Mirzaei, Ardalan; Rijcken, Claudia (Academic Press, 2023)
Pharmaceutical Care in the Digital Revolution: Blending Digital with Human Innovation, Second Edition provides readers with an updated view on how to use technology to improve pharmaceutical care (PC) and enhance drug outcomes with digital tools. Organized into four parts, including Global Healthcare Systems Under Pressure, Digital Advances to Innovate Pharmaceutical Care Journeys, Conditions to Drive Combinatoric Pharma-Digital Innovation, and What to do Tomorrow as a Pharmaceutical Care Leader, the book further examines digital developments that will optimize the PC process and prepare stakeholders for a dynamic future that will optimize the life of patients against a sustainable cost model. This edition also discusses recent advances in the digital health arena that will change the way we approach healthcare and prevention while also providing interactive links to lectures and technologies, tutorials on how to implement advances in your own working environment, and examples of pharmacists who are successful in building synergy between digital and pharma.